Cell-specific expression of Hfe determines the outcome of Salmonella enterica serovar Typhimurium infection in mice - Nairz, Manfred; Metzendorf, Christoph; Spasić Vujić, Maja; Mitterstiller, Anna-Maria; Schroll, Andrea; Haschka, David; Hoffmann, Alexander; Raffay, Laura von; Sparla, Richard; Huck, Christian W.; Talasz, Heribert; Moser, Patrizia L.; et al. (Haematologica, 2021)
Mutations in HFE cause hereditary hemochromatosis type I hallmarked by increased iron absorption, iron accumulation in hepatocytes and iron deficiency in myeloid cells. HFE encodes an MHC-I like molecule, but its function in immune responses to infection remains incompletely understood. Here, we investigated putative roles of Hfe in myeloid cells and hepatocytes, separately, upon infection with Salmonella Typhimurium, an intracellular bacterium with iron-dependent virulence. We found that constitutive and macrophage-specific deletion of Hfe protected infected mice. The propagation of Salmonella in macrophages was reduced due to limited intramacrophage iron availability for bacterial growth and increased expression of the anti-microbial enzyme nitric oxide synthase-2. By contrast, mice with hepatocyte-specific deletion of Hfe succumbed earlier to Salmonella infection because of unrestricted extracellular bacterial replication associated with high iron availability in the serum and impaired expression of essential host defense molecules such as interleukin- 6, interferon-g and nitric oxide synthase-2. Wild-type mice subjected to dietary iron overload phenocopied hepatocyte-specific Hfe deficiency suggesting that increased iron availability in the serum is deleterious in Salmonella infection and underlies impaired host immune responses. Moreover, the macrophage-specific effect is dominant over hepatocytespecific Hfe-depletion, as Hfe knockout mice have increased survival despite the higher parenchymal iron load associated with systemic loss of Hfe. We conclude that cell-specific expression of Hfe in hepatocytes and macrophages differentially affects the course of infections with specific pathogens by determining bacterial iron access and the efficacy of antimicrobial immune effector pathways. This may explain the high frequency and evolutionary conservation of human HFE mutations.
Pre-published: October 13, 2020
Gesehen am 23.02.2022